Successful Treatment of Post-dural Puncture Headache with Sphenopalatine Ganglion Block in Post-cesarean Section Patient: A Case Report - Asmara, Rohedi Yosi; Sukmono, Besthadi; Pryambodho, Pryambodho (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Post-dural puncture headache is a symptom often found in post-operative patients who receive spinal anesthesia. Therefore, therapy to reduce patient complaints becomes a comparison to find the best alternative for action. This case discusses post-dural puncture headache risk factors in post-cesarean section patients and sphenopalatine ganglion block as an alternative pain intervention. CASE PRESENTATION: The patient is a 26-year-old woman, G1P0A0, 80 kg, who presented for the first cesarean delivery at 37 weeks of gestational age due to concern for breech presentation. The patient was put into a sitting posture before the spinal anesthetic was administered. She was offered spinal-epidural anesthesia using a Quincke type 26 G spinal needle. The patient was successfully given one shot of spinal anesthesia using the paramedian approach technique. The medication of 1 g paracetamol was given at 8 h intervals as post-operative analgesia. On post-operative day 2, the patient was consulted by the anesthesiologist, and the patient reported an 8/10 severity positional headache on the numerical rating scale. Intranasal SPGB has been performed on the patient with lidocaine spray 20 mg. The patient’s headache reduced from an NRS of 8/10 to a 6/10 after 5 min of sphenopalatine ganglion block. Twenty-four hours after the procedure, the patient can sit up, lower the neck tension and headache, and resume activities independently. The patient was released the next day with a manageable headache. In 48 h post-block, the patient was called and inquired about PDPH and almost no headache with various positions. CONCLUSION: SPG block can be a minimally invasive treatment for PDPH. The faster PDPH is treated using an SPG block, the better the patient’s pain scale outcome. Several studies have shown that patients who received SPG block therapy did not continue to get EBP.